Assessing the dropout rate of the expanded programme on immunisation in Asutifi District. - Akutteh, Hanson Mensah (2011)
A dissertation submitted to the School of Graduate Studies (Kwame Nkrumah University of Science and Technology) in partial fulfillment of the requirements for the Master of Public Health Degree In The Health Services Planning And Management, 2008